Magnesium-doped biphasic calcium phosphate nanopowders via sol-gel method - Sopyan, Iis; Abdul Rahim, Toibah; Ahmad, Zainal Arifin (Nova Science Publishers, Inc, 2010)
Biphasic calcium phosphate (BCP) is a mixture of non-resorbable hydroxyapatite (HA) and the resorbable tricalcium phosphate (TCP) is an interesting material for bone implant as it shows biocompatibility and bioactivity to tissue bone. More efficient bone repair was widely been known in BCP than HA alone. Good implant materials should be biodegradable as it can degrade inside the bone and defect simultaneously with the formation of a new bone. In this study BCP has been doped with magnesium through sol-gel method. Doping of magnesium ions into BCP will results in biological improvement as the ion will cause the acceleration of nucleation kinetics of bone minerals. Magnesium depletion adversely affects all stages of skeletal metabolism, leading to decrease in osteoblastic activities and bone fragility. Magnesium–doped biphasic calcium phosphate (Mg-BCP) powders were successfully prepared using Ca(NO3)2.4H2O and (NH4)2HPO4 as the precursors and Mg(NO3)2.6H2O as the source of the dopant. Morphological evaluation by FESEM measurement showed that the particles of Mg-BCP were tightly agglomerated, with primary particulates of 50-150 nm diameters. FESEM result also showed that doping of magnesium into BCP particles caused fusion of particles leading to more progressive densification of particles as shown by higher concentration of magnesium doping. Successful incorporation of Mg into BCP lattice structure was confirmed by higher crystallinity of Mg-BCP and by shifting of tricalcium phosphate (TCP) peaks in XRD